Gender disparity in telehealth usage in Bangladesh during COVID-19 - Saanjaana Rahman; Sajid Amit; Abdulla - Al Kafy (Elsevier, 2022)
Background and aims: Telehealth allows healthcare workers to see patients virtually in locations that were not accessible previously, which has reduced cost and time and saved lives. The research aims to examine gender disparity among telehealth usage during the pandemic in 2020. This study will leverage a timely national experiment to evaluate the users of telehealth across the Bangladeshi population. Methods: We obtained de-identified data for 200 patients among outpatient telehealth visits from Global Health Data Exchange as it captured telehealth use throughout Bangladesh. Results: The analysis showed that male patients had a higher dependency on telehealth than female patients. 14% of the female patients opted for telehealth visits only with 57% cases of missed doses of medication, compared to males with 20% of them choosing telehealth visits and 29% missing their doses of medication. We found that the youngest age group, 16-25, had the highest dependence on telehealth compared to any other age group, and the lowest dependence was among the oldest age group of 45 years and above. Conclusions: There was a strong association between telehealth use and gender disparity with p value ​= ​0.02 ​< ​0.05. Longitudinal and geographical data are needed to understand more about the gender disparities and impact in telehealth utilizations.